Odpowiedzi

2010-02-04T18:20:39+01:00
F)2t-(3t+1)=6
2t - 3t - 1 = 6
-t = 7
t = -7

g)-(4+x)=2(3-x)
-4 - x = 6 - 2x
x = 10

h)3(y+6)-y+2(y+9)
gdzie tu jest znak =

i)(x-7)-2(3x+5)=3
x - 7-6x - 10 = 3
-5x = 20
x = -4
Najlepsza Odpowiedź!
2010-02-04T18:23:37+01:00
Rozwiąż równania:
f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1||-1
t=-7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)=y+2(y+9)
3y+18=y+2y+18
0=0
ALBO
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=3+17
-5x=20||-5
x=-4
2010-02-04T18:26:31+01:00
1
2t-3t-1=6
-t=7 /:(-1)
t=-7
2
-(4+x)=2(3-x)
-4-x=6-2x
x=10
3
nie wiem gdzie jest=
4
(x-7)-2(3x-5)=3
x+3x=3+7+2-5
4x=7 /:4
x=1,75